2021
DOI: 10.2176/nmc.oa.2020-0430
|View full text |Cite
|
Sign up to set email alerts
|

Higher Non-fasting Serum Triglyceride Preceding the Carotid Stenosis Progression

Abstract: The present study was conducted to investigate whether non-fasting serum triglyceride (TG) levels can be used to assess a risk for the progression of carotid artery stenosis. This was a single-center retrospective study. Consecutive 96 patients with ≥50% stenosis of at least unilateral cervical internal carotid artery and normal fasting serum low-density lipoprotein cholesterol (LDL-C) levels of ≤140 mg/dL were followed up for at least 1 year (mean, 3.1 years), and clinical variables were compared between pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
(46 reference statements)
0
12
0
Order By: Relevance
“… 28 ApoB is the main apolipoprotein of chylomicrons and LDL-C, and may contribute to atherogenesis. 29 The ApoB/ApoA-I ratio was found to be associated with CAD risk. 30 , 31 Recent prospective studies indicated that low ApoA-I levels, high ApoB levels and the ApoB/A-I ratio may be even better predictors of CAD risk than traditional lipid parameters.…”
Section: Discussionmentioning
confidence: 99%
“… 28 ApoB is the main apolipoprotein of chylomicrons and LDL-C, and may contribute to atherogenesis. 29 The ApoB/ApoA-I ratio was found to be associated with CAD risk. 30 , 31 Recent prospective studies indicated that low ApoA-I levels, high ApoB levels and the ApoB/A-I ratio may be even better predictors of CAD risk than traditional lipid parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The statement sets the upper reference value of postprandial TG to 175 mg/dL, which is 25 mg/dL higher than the fasting reference TG value of 150 mg/dL [ 11 ]. Serum TG levels are generally increased for six to eight hours after a standard diet [ 6 , 12 ], and it may be feared that TG levels can be increased more than the estimated 25 mg/dL variance when a patient consumes a high-fat meal prior to blood sampling, leading to the misrepresentation of the clinical significance. Therefore, serum TG values have been regularly measured exclusively after eight to twelve hours of fasting [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Idei et al also revealed that a higher mean value of non-fasting TG during a 1-year period was more frequently associated with the appearance of carotid plaques and was a superior predictor to either the mean and one-point fasting TG values or one-point non-fasting TG ones in 115 patients with type-2 diabetes mellitus [ 18 ]. As to carotid artery stenosis, our recent study showed that elevated non-fasting TG level at the first visit to neurosurgical clinic to evaluate ≥50% carotid artery stenosis was an independent risk factor of subsequent progression of the disease in 96 patients under good control of fasting LDL-C levels [ 6 ]. Additionally, the study reported that a cut-off value of non-fasting TG to discriminate carotid stenosis progression was 169.5 mg/dL for less severe-side carotid arteries with the baseline stenosis of <50%, and 154.5 mg/dL for worse-side carotid stenosis of ≥50%, suggesting that more strict control of non-fasting TG was necessary to prevent the stenosis progression for a higher degree of carotid artery stenosis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations